1986
DOI: 10.1002/hlca.19860690804
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Structure of Substance P. III. Secondary Structure of Substance P in 2,2,2‐Trifluoroethanol, Methanol, and on Flat Lipid Membranes Studied by Infrared Spectroscopy

Abstract: IR data of the neuropeptide substance P (1) and its synthetic segments des-(Arg'-Gin')-substance P (6), des-(Arg'-Pro4)-substance P (4), des-(Arg'-Lys3)-substance P (3), and des-Arg'-substance P (2) indicate predominant p-structures in the solid state and a-helical structures in CF,CH20H (amide I band shape analysis). In MeOH, the spectra of 1 suggest a partly helical structure. On membranes prepared from 1-palmitoyl-2-oleoyl-snglycero-3-phosphocholine, a C-terminal a-helix consisting of 8 or 9 peptide bonds a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
46
1

Year Published

1990
1990
2001
2001

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 24 publications
2
46
1
Order By: Relevance
“…12 attributed this large upfield shift in ␦(NH) in Gly 9 to a general feature for glycine in peptides with the sequence Tyr/Phe-X-Gly observed by Kemmink et al 53 However, Chassaing et al 50 suggested that folding at the C-terminus (Gly-Leu-Met) of SP in solution results in the large chemical shift differences of Gly 9 12 for SP under similar conditions than to that for SP in 15 mM SDS reported by Young et al 13 The difference from the latter can either be due to the secondary structure, to the binding pattern, or both. The use of a lower micelle-to-peptide molar ratio (12.5:1), especially with the micelle concentration close to the cmc for SDS, and a lower pH value by Young et al 13 may account for this difference.…”
Section: Partitioning Of [Tyrmentioning
confidence: 94%
See 3 more Smart Citations
“…12 attributed this large upfield shift in ␦(NH) in Gly 9 to a general feature for glycine in peptides with the sequence Tyr/Phe-X-Gly observed by Kemmink et al 53 However, Chassaing et al 50 suggested that folding at the C-terminus (Gly-Leu-Met) of SP in solution results in the large chemical shift differences of Gly 9 12 for SP under similar conditions than to that for SP in 15 mM SDS reported by Young et al 13 The difference from the latter can either be due to the secondary structure, to the binding pattern, or both. The use of a lower micelle-to-peptide molar ratio (12.5:1), especially with the micelle concentration close to the cmc for SDS, and a lower pH value by Young et al 13 may account for this difference.…”
Section: Partitioning Of [Tyrmentioning
confidence: 94%
“…This may be a result of a less definite conformation for this peptide in SDS than in DPC. The NOE-derived distance restrained molecular modeling shows an approximate 3 10 -helical conformation over the midregion Pro 4 -Gly 9 . The dihedral angles and of this region range from Ϫ47°to Ϫ89°, and from 2°to Ϫ38°, respectively.…”
Section: Partitioning Of [Tyrmentioning
confidence: 99%
See 2 more Smart Citations
“…[11][12][13][14][15][16] Different studies have shown that SP has no preferred conformation in aqueous solutions. 11,12,15 A mixed R-helix/folded structure in methanol has been proposed with five hydrogen bonds determining the conformation of the molecule.…”
Section: Introductionmentioning
confidence: 99%